2015
DOI: 10.17795/ijpbs-842
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Pattern in Suicide in Iraan

Abstract: Background:Various studies have shown a seasonal pattern in suicide in the developed societies; however, this pattern is not taken into consideration in most countries including Iran.Objectives:The current paper studied the seasonal pattern of committing suicide in Northern Iran.Materials and Methods:The present study was a longitudinal study with time series features. Subject included suicide attempts recorded by emergency wards of all hospitals in Mazandaran province, Iran. The variable time, in this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The age period between 21 and 40 years old is reported as a critical stage of life for men and women in Iran due to ongoing family and career responsibilities (Amoli et al., 2018). However, the dominant suicide age is different in various parts of Iran (Moqaddasi Amiri et al., 2015) likely due to the unique nature of problems and social tensions that are present among the various provinces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age period between 21 and 40 years old is reported as a critical stage of life for men and women in Iran due to ongoing family and career responsibilities (Amoli et al., 2018). However, the dominant suicide age is different in various parts of Iran (Moqaddasi Amiri et al., 2015) likely due to the unique nature of problems and social tensions that are present among the various provinces.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is a complex human behavior which is correlated with serious mental health disorders such as depression, personality disorders, bipolar depression, adjustment disorders, etc. particularly in younger populations (Moqaddasi Amiri et al., 2015). In the developing world, people are living longer with chronic life-limiting conditions and may want individual choice in regards to decisions surrounding death (Olsen et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in 2013, suicide resulted in 842,000 deaths [ 3 ]. Globally, suicide is the 15th leading cause of death in all ages [ 4 ] and the fourth in ages of 15–44 years [ 5 ]. In addition, for each successful suicide attempt, there are 10–40 failed suicide attempts as well [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] For example, in Mazandaran province, seasonal pattern of attempted suicide cases recorded by emergency wards of all hospitals were examined, which the results showed the highest rates of attempted suicide were in June and November, and the lowest rate was in the winter. [ 27 ] Other studies that examined suicide seasonality pattern in Ilam province showed that significant suicide seasonality was observed with one peak in the spring and one in the autumn. [ 28 29 ] Furthermore, another study reported the relationship between completed suicide and seasons of the year in south of Iran.…”
Section: Discussionmentioning
confidence: 99%